EFFECTS OF EXPORTS, IMPORTS AND INVESTMENTS IN THE AGRICULTURAL SECTOR AND RUPIAH EXCHANGE RATE ON ECONOMIC GROWTH IN INDONESIA - Husna, Raudhatul; Sofyan; Usman, Mustafa (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
The economy of a country, especially Indonesia, is influenced by many factors which include exports, imports, investment in agriculture and changes in exchange rates. The purpose of this study was to examine the effect of the rupiah exchange rate, exports, imports and investment on economic growth in Indonesia and to test the effect of the shock of the rupiah exchange rate variables, exports, imports and investment on economic growth in Indonesia. The analytical method used is the VAR (Vector Autoregression) model. The basic form of the VAR model used treats all variables symmetrically regardless of the dependent variable or the independent variable. In this study using five variables. The variables used are the exchange rate (RER), exports (X), imports (M), investment (I) and economic growth (GDP). The results of the study concluded that there was a one-way relationship between exchange rate variables, exports and imports to economic growth. There is a two-way relationship in the exchange rate variable affecting exports and imports. While there is no significant relationship between the investment variable and economic growth and the exchange rate shock is responded negatively by economic growth at the beginning of the period, besides that the export shock is responded positively at the beginning of the period and the import shock is responded positively at the beginning of the period and the investment shock is responded positively by economic growth in first period.